Serum Soluble CD40 Ligand in Predicting Simple Appendicitis and Complicated Appendicitis at Different Time Points in Children - Huang, Wun-Yan; Chen, Chun-Yu; Chang, Yu-Jun; Lee, En-Pei; Wu, Han-Ping (Frontiers in Pediatrics, 2021)
Objectives: Appendicitis is a common abdominal emergency in children. It is difficult for clinicians to distinguish between simple appendicitis (SA), gangrenous appendicitis (GA), and ruptured appendicitis (RA) in children based on physical and current laboratory tests. Abdominal computed tomography with the disadvantage of excess radiation exposure is usually used in the emergency room for appendicitis surveys. Serum soluble CD40 ligand (sCD40L) is an inflammatory biomarker. This study aimed to use sCD40L to distinguish SA, GA, and RA. Methods: All patients aged less than 18 years old with suspected appendicitis were tested once for serum sCD40L within 72 h of appendicitis symptoms. We compared sCD40L levels of SA, GA, and RA individually on days 1, 2, and 3 in patients with normal appendix (NA), a total of nine subgroups. Thereafter, the diagnostic performance of sCD40L in predicting appendicitis and the receiver operating characteristic curves were carried out. Results: Of 116 patients, 42 patients had SA, 20 GA, 44 RA, and 10 NA. We found six subgroups with significant p values of sCD40L predicting appendicitis as follows: SA on day 2, GA on days 2 and 3, and RA on days 1 to 3. The sensitivity and specificity of sCD40L at the best cutoff point with 178 pg/mL in these six subgroups range from 0.75 to 1.00 and 0.90, respectively. Conclusions: SCD40L is a good predictor of pediatric appendicitis. Clinicians can use sCD40L to distinguish from SA, GA, and RA in children with suspected appendicitis.